Identifying Key Concepts of the Language of Desire and the Language of Ethics in Dialogic Literary Gatherings - Garazi López de Aguileta; Víctor Climent-Sanjuán; Adriana Aubert; Alba Crespo-López; Lena de Botton; Carme Garcia-Yeste; Marta Soler-Gallart (International Journal of Sociology of Education)
Given the high prevalence of gender violence among adolescents and youth, research has underscored the importance of preventing it from an early age. The literature has clarified that the prevention of gender violence requires the union of the language of desire and of ethics to promote egalitarian relationships as desirable. Nevertheless, there is a need for a more in-depth and extensive analysis of the key concepts that emerge in DLG, implemented in diverse contexts to better understand their potential as a space for the prevention of gender violence. To contribute to filling this gap, this study explores key concepts of desire and ethics that adolescents surface in DLG implemented in 5 Learning Communities have in common. To that end, 26 observations in 9 different DLG groups with students aged 10-15 and 45 interviews with students and teachers were conducted. Results show one key concept of desire and ethics in these DLG: many students reject violence and peer pressure. Implications of these findings for the prevention and overcoming of gender violence are discussed.